Model for the evaluation of usability of scientific workflows - Amelia, Abd Rahman (2019)
Scientific workflows are extensively important among scientific communities, which unified scientific data, analysis, simulation tasks to conduct any computational experiments. Existing scientific workflow systems, which consist of dozens of detailed and systematic steps, enable scientists to create and visualize scientific processes without much difficulty. Regardless of their potential for advancement in science, there are still improvement that can be made especially in unification of scientific workflow systems since different scientific communities required different notations to model. As scientific workflows evolved over time, it is also difficult for scientific communities to discover suitable scientific workflows for their task. In this research, evaluation of usability of scientific workflows is being done since it is a key characteristic of determining the success of any software system. Empirical study was applied for the usability evaluation, based on creation of questionnaire to develop survey and statistic hypotheses checking. Statistical Package for the Social Sciences (SPSS) was used to analyse the data after responses were collected. For validation of survey, the collection of data from 101 respondents of scientific community and developers of scientific workflow systems was collected then the reliability analysis (Cronbach’s Alpha), One Sample t Test, factor analysis (KMO and Bartlett’s Test), ANOVA test were used. MATLAB was use for development of coding for Cronbach’s Alpha. Results of this research, which is the proposed model of usability of scientific workflows, will help to upgrade the quality attributes in scientific workflow systems.